The use of cash by households in the euro area - Henk Esselink; Lola Hernández (European Central Bank (ECB), 2017)
Although euro banknotes and coins have been in circulation for fifteen years, not much is known about the actual use of cash by households. This paper presents an estimation of the number and value of cash transactions in all 19 euro area countries in 2016, based on survey results. It presents an extensive description of how euro area consumers pay at points of sale (POS). The aim of this study is to shed light on consumers' payment behaviour and in particular to improve the understanding of consumers' payment choices at POS, based on a large sample of countries. Therefore, it provides central banks and relevant payment system stakeholders with fundamental information for the development of their policies and strategic decisions that can contribute to improving the efficiency of the cash cycle and the payment system as a whole. Previous estimates of the value of cash usage by households in the euro area date from 2008. Since then some central banks have carried out their own research on cash usage. This paper is the first study to measure the transaction demand for cash in the euro area. The results show that in 2016 around 79% of all payments at POS were made with cash, 19% with cards and 2% with other payment instruments. In terms of value, the market share of main payment instruments was 54% for cash, 39% for cards and 7% for other instruments. However, results show substantial differences between euro area countries.
Keywords: E41; E58; D12; D14; 330; payment behaviour; money demand; payment systems; cash; consumer choice